“Alejandra”: exposición fotográfica sobre el uso del autorretrato como herramienta de autodescubrimiento - Chavez Aguilar, Diana Carolina (2021)
Alejandra is a visual project made up of nine images presented in audiovisual format that narrate the author's personal exploration process through self-portraiture. These photographs compile the evolution of the link between the camera and the photographed; that ends up revealing itself as the relationship of the subject in herself and of the subject as part of society. Considering the self-portrait as a tool for introspection and selfdiscovery, this work presents reflections on women´s body and their role in society based on the rediscovery of personal experience from feminist theories. Likewise, through contact with artistic practices made by other women, and dialogue with experts within photography and academic studies, it has sought to influence the importance of proposals that unite art and feminism to combat the manifestations of sexism that are still present in our society. This work intends, within its possibilities, to be part of this movement.